Extra‐ampullary duodenal adenoma: a clinicopathological study. Issue 2 (5th May 2017) - Hijikata, Kazunori; Nemoto, Tetsuo; Igarashi, Yoshinori; Shibuya, Kazutoshi
Abstract : Aims: Extra‐ampullary duodenal adenoma (EADA) is a rare condition with poorly described clinicopathological details. In this study, we aimed to characterize EADA clinicopathologically. Methods and results: We performed a retrospective review of 44 serial cases of EADA. Each EADA was categorized as either gastric‐type ( n = 5) or intestinal‐type ( n = 39). All gastric‐type adenomas were located in the first portion of the duodenum and exhibited a pedunculated shape. Gastric‐type adenomas were classified into two subtypes: pyloric gland and foveolar. The former consisted of mucin 6 (MUC6)‐positive glands covered with MUC5AC‐positive cells, whereas nearly all the latter consisted of MUC5AC‐positive cells. When EADAs were categorized into high and low grades, approximately 40% (16 of 44) were high‐grade. The high‐grade adenomas were significantly larger than the low‐grade adenomas (19.4 ± 8.6 mm versus 11.8 ± 5.1 mm, P = 0.021), and all adenomas greater than 20 mm in largest diameter were categorized as high‐grade adenomas. Among 16 individuals who underwent total colonoscopy before or after duodenal mucosal resection, nine had a colorectal neoplasm, and all nine duodenal lesions were of the intestinal phenotype. Conclusions: We clarified the clinicopathological characteristics of gastric‐ and intestinal‐type EADAs. EADAs greater than 20 mm at the largest diameter were consistently high‐grade, and are thought to have the potential to progress to adenocarcinoma. These findings should be helpful for the clinical management of EADA.